Don't stare, unless you don't want to remember: Maintaining fixation compromises autobiographical memory retrieval. Issue 2 (7th February 2019) - Lenoble, Quentin; Janssen, Steve M. J.; El Haj, Mohamad
ABSTRACT: This study has developed an original approach to the relationship between eye movements and autobiographical memory, by investigating how maintained fixation could influence the characteristics of retrieved memories. We invited participants to retrieve autobiographical memories in two conditions: while fixating a cross at the centre of a screen and while freely exploring the screen. Memories retrieved during the maintained fixation condition were less detailed and contained less visual imagery than those retrieved during the free-gaze condition. Memories retrieved during the maintained fixation condition were retrieved slower and took less time to describe than those retrieved during the free-gaze condition. As for the characteristics of eye movements, analysis showed fewer and longer fixations as well as fewer saccades in the maintained fixation than in the free-gaze condition. Maintaining fixation is likely to tax cognitive resources that are necessary for the reconstruction of autobiographical memory. Our findings demonstrate how maintained fixation may result in a more effortful construction of autobiographical memory and memories with lower spatiotemporal specificity and poorer mental images.